Comportamento e interações ecológicas entre predadores terrestres no meio hipógeo de Presidente Olegário-MG - Resende, Leonardo Palloni Accetti (2015)
The subterranean environment has a set of unique ecological characteristics, like the low thermic variation, high relative humidity of the air, areas with permanent and total absence of light and the dependence of food input of the surface. Those characteristics promote distinguish ecological conditions that drive and modify the population structure and the ecological interactions of the organisms that live in the subterranean realm, generating communities unique in diversity and structure. This dissertation is the result of two years of work in a peculiar cave system located on Presidente Olegário municipality, Northwest of Minas Gerais state. We monitored seven cavities (Lapa Vereda da Palha, Lapa da Fazenda São Bernardo, Lapa Zé de Sidinei, Lapa Arco da Lapa, Lapa do Moacir, Toca do Charco e Gruta da Juruva), with the intention of answered the following questions: What is the diversity of terrestrial predators that occurs in these caves? Is the distribution of these predators in these caves random or standardized by competitive and/or predation pressures? How these predators behave? Is their behavior telling us something about their relation with the subterranean environment? To do this, we realized five fild works in that caves, where we collected the invertebrate fauna using the manual active search and Winkler extractors. Beyond that we realized field observations of the natural history and laboratory tests of five species of predators that was selected for it. We found a marvelous diversity of predators (79 species belonging to Araneae, Pseudoscorpiones, Opiliones, Scorpiones, Heteroptera, Scolopendromorpha, Geophilomorpha e Lithobiomorpha). The spiders was the most diverse and abundant of them all. Despite of all that huge variety of species, their spatial distribution inside the caves was not related with hard competition among them. The laboratorial tests show that their often coexist and share the space instead of fight and prey each 4 other. Each one of the five species selected for the tests uses the space, foraging and interact with conespecifics in a different way, then we consider that behavior differentiation an important factor of niche segregation that reduces the competition pressures. Finally, we consider the structure and ecological features of each cave another factor that can contribute to the reduction of competition pressures and allowed these caves to sustain this high number of species. Beyond that, we observed that harvestman have a richer behavioral repertorie than the spiders, they are more active, interacting with conespecifics and they spend more time moving through space. However, when we compared the behaviors of these species with their epigean relatives, we observed that there is no significant difference among then. We hypothetize that lack of difference is coused by the fact that the observed behaviors are typical for their taxonomic groups, thus their occurrence in the caves as troglophyles (Eusarcus hastatus, Loxosceles similis, Isoctenus sp. e Enoploctenus cyclothotax) or as trogloxenes (Mitogoniella taquara) couldn t be interpreted as a factor of pressure on their expressed behaviors, probably being instead an important exaptation for the establishment of the populations of these species.